2023
DOI: 10.3390/f14091746
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth Characterization and Antioxidant Responses of Phellodendron chinense Seedling in Response to Four Soil Types at Three Growth Stages

Yao Yang,
Yun-Yi Hu,
Wen-Zhang Qian
et al.

Abstract: Soil type is an important environmental factor that affects plant growth and development, especially during the early growth stage. In this study, P. chinense (Phellodendron chinense) seedlings were cultivated on red soil (RS), yellow soil (YS), acidic purple soil (ACPS), and alkaline purple soil (ALPS), and the influence of soil types on the growth parameters and physiological responses at three growth stages were investigated. The results show that soil types and growth stages can significantly influence see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Previous reports showed that plant height, base diameter, and biomass of Jatropha curcas plants are related to soil types, and the growth status of different species varies significantly in different types of soils [37]. Previous studies also suggested that Phellodendron chinense, Ricinus communis, and Firmiana simplex seedlings show significant differences in seedling height, basal diameter, and total biomass when they are cultured in RS, YS, ALPS, and ACPS [6,38,39]. These variations are due to different soil types with different physical, chemical, and microbial community structures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous reports showed that plant height, base diameter, and biomass of Jatropha curcas plants are related to soil types, and the growth status of different species varies significantly in different types of soils [37]. Previous studies also suggested that Phellodendron chinense, Ricinus communis, and Firmiana simplex seedlings show significant differences in seedling height, basal diameter, and total biomass when they are cultured in RS, YS, ALPS, and ACPS [6,38,39]. These variations are due to different soil types with different physical, chemical, and microbial community structures.…”
Section: Discussionmentioning
confidence: 99%
“…Soil, as a basic condition for agricultural production, has a significant impact on plant growth, yield, and biochemical contents [6,8]. Growth parameters, like seedling height, ground diameter, and biomass, can reflect the growth status of plants in response to various environmental conditions, like soil [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations